Preparation of photo-crosslinked hyaluronic acid/silk fibroin hydrogel for promoting wound healing - Shujing Li; Wensheng Pan; Maohu Chen; Ruyue Wang; Feng Chen (Exploration of BioMat-X)
Aim: Acute cutaneous injuries and refractory chronic wounds represent prevalent clinical challenges in daily life. To address the impediments to wound healing, we propose a novel hydrogel-based therapeutic approach designed to prevent bacterial invasion, mitigate infection-induced persistent inflammatory responses, and reduce excessive oxidative stress, thereby enhancing the wound healing process. Methods: This study presents a method for preparing hyaluronic acid/silk fibroin (HA/SF) composite hydrogels via photo-crosslinking. HA and SF were respectively modified via methacrylation and glycidyl methacrylate to synthesize HAMA and SFMA. Mussel-inspired catechol groups were then grafted onto HAMA chain segments to prepare precursor HAC. Under photo-initiator LAP, polymerization was triggered to ultimately form a hydrogel network integrating mechanical toughness and tissue adhesiveness. Composite hydrogels with varying degrees of crosslinking are synthesized by adjusting the SFMA content. Results: The results demonstrate that this hydrogel can effectively achieve hemostasis within 20 seconds. Lap shear testing revealed that the HASF-gel-2 hydrogel exhibited the highest maximum adhesive strength of 160.3 kPa among all experimental groups. Furthermore, while the cell viability of the control group was normalized to 1, the composite hydrogel groups displayed values of 1.015, 1.085, 1.136, and 1.263, respectively, indicating favorable biocompatibility. The appropriate incorporation of SF was shown to enhance cellular proliferation. On day 3 post-wounding, the HASF hydrogel group demonstrated a wound closure rate of 41.7%, outperforming commercial products under identical conditions. Conclusions: In rat wound models, the HASF composite hydrogel significantly accelerated wound healing progression.